Una concepción del tiempo no-lineal en dos lenguas: el maya yucateco colonial y actual y la lengua de señas maya yucateca - Olivier Le Guen (Journal de la Société des Américanistes)
This work shows to what extent there exists a distinctive (Yucatec) Maya conception of time, in which time is not metaphorically linear and can be conceived as “structurally cyclical”. I will take examples from two languages that can be considered to belong to the same culture, namely Yucatec Maya culture. The first is Yucatec Maya considered from a diachronic perspective, with examples from contemporary Maya, as well as examples of colonial Maya taken from the Books of Chilam Balam. The second language considered is Yucatec Mayan Sign Language, an emerging language that recently appeared in Mayan villages where deaf persons were born. In order to communicate without using an oral language, deaf persons and their families have invented sign languages that have similar characteristics in different villages. This work specifically analyses the metaphors used to talk about time and aims to demonstrate that, at least until recently, the western conception of time has not had an influence on the Maya.